2013
DOI: 10.1017/s1355617713001227
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Psychosocial Phenotype of Young Children with Neurofibromatosis-1

Abstract: Children with neurofibromatosis-1 (NF1), a neurodevelopmental disorder resulting from a mutation of the NF1 gene (17q11.2), often have difficulties with learning and attention, but there is little research in the early childhood years. In this study, the cognitive and psychosocial functioning of 40 young children with NF1 (ages 3 through 6) was examined and compared both to normative data and to a contrast group comprised of unaffected siblings and community members matched for age and socio-economic status (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
21
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 59 publications
5
21
2
1
Order By: Relevance
“…The present study investigates the development over time of parent‐reported behavioral problems in young children with NF1 and the influence of intelligence, language development, and early behavioral problems. In accordance with other studies (Klein‐Tasman et al, ), we did not find an elevated level of behavioral problems in young children (mean age 4;5 years), but we did find more internalizing problems at a later age (mean age 7;11 years), compared to a normative sample. Higher rates of internalizing problems indicate more anxious, withdrawn, and depressed behavior and/or more somatic complaints.…”
Section: Discussionsupporting
confidence: 92%
“…The present study investigates the development over time of parent‐reported behavioral problems in young children with NF1 and the influence of intelligence, language development, and early behavioral problems. In accordance with other studies (Klein‐Tasman et al, ), we did not find an elevated level of behavioral problems in young children (mean age 4;5 years), but we did find more internalizing problems at a later age (mean age 7;11 years), compared to a normative sample. Higher rates of internalizing problems indicate more anxious, withdrawn, and depressed behavior and/or more somatic complaints.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the age for ASD diagnosis in the NF1 + ASD group was on average 10.65 years, which can be easily situated in between these two important developmental phases of 8–10 and 11–13 years of age. These results are in line with the general idea that other than social problems are on the forefront at a younger age [Klein‐Tasman et al, ; e.g., cognitive vulnerabilities, attention problems], while also confirming the fact that some early screening tools fail to identify NF1 children having difficulties in social interaction and communication [Tinker et al, ]. It will be very important to arrange future research in such a way that it includes extensive and systematic screening and/or assessment for social abilities at an early age in a longitudinal approach while not being limited to a one‐off assessment.…”
Section: Discussionsupporting
confidence: 82%
“…This moderately higher magnitude of internalizing symptoms in our cohort as compared to past studies could be related to a few factors, including sample characteristics or differences in psychometric properties of the measures used (BASC‐2 vs. CBCL). The most apparent discrepancy in scores on anxiety and depression measures across studies appears to be between our study and that of Klein‐Tasman et al (), which enrolled preschool‐aged children with NF1 (ages 3–6). Klein‐Tasman and colleagues found no significant parent‐rated group mean differences between the NF1 group and a typically developing comparison group for anxiety or depressive symptomatology on the BASC‐2.…”
Section: Discussioncontrasting
confidence: 72%